Fragrant Attraction: Aromatics in Premodern Chinese History - Liu, Yan (History compass, 2024)
This essay surveys the history of aromatics in China from antiquity to the 17th-century. Compared to the extensive study of the spice trade that has shaped world history, much less has been explored on the movement of these fragrant substances from their natural habitats in South, Southeast, and West Asia to China. By reviewing both early and recent scholarship on the topic, the essay demonstrates the wide circulation of these materials along the Silk Roads enabled by multiethnic traders, religious practitioners, and diplomats. Once imported into China, they acquired diverse uses in healing, food culture, and religious practices that generated new knowledge and transformed Chinese society. Their unique smells could also alter the ways of prescribing medicines and relishing food, and enhance the bodily experience of the devoted. An in-depth study of aromatics using a multidisciplinary approach will not only deepen our understanding of premodern Chinese society but also offer an alternative worldview of aromatics that counteracts the one habituated by the “rise of the West” in early modern times.